Tiktok dan Shopee Live: Solusi Transformasi Pemasaran dan Peningkatan Daya Saing UMKM Kacang Intip - Marpaung, Durahman; Bakti, Surya (CV. IRA PUBLISHING, 2023)
In Batu Bara Regency, North Sumatra, Indonesia, significant economic transformation has occurred by developing Micro, Small, and Medium Enterprises (MSMEs) based on chili agriculture. Lubuk Cuik Village, one of the region's largest chili producers, has become the focus of economic empowerment through MSMEs. The community service program